Sosialisasi Kompor Gasifikasi KOMAS Untuk Kebutuhan Memasak Di Desa Batu Belah Kabupaten Kampar - Zulfansyah Zulfansyah; Hari Rionaldo; Zuqni Meldha; Nirwana Nirwana; Maria Peratenta; Sri Helianty (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The shortage of availability and increasing prices of Liquefied Natural Gas (LPG) encourage some people to use firewood as an alternative to traditional cooking fuel. The utilization of conventional stoves for combustion results in the generation of carbon monoxide (CO) emissions which can be dangerous to human health. Gasification stoves produce less CO emissions than conventional stoves and produce thermal efficiencies up to 35%. The shortage and high expense of LPG can be avoided by using biomass waste, such as twigs, wood chips, and palm fronds, as fuel for gasification stoves instead of kerosene or LPG. The gasification stove used in the socialization was designed based on the dimensions of the Champion Stove Top-Lit Up Draft. Wood logs that have been cut to a size of 6–9 cm and a width of 1 cm are utilized as fuel. 1.5 liters of water were successfully boiled for nine minutes by KOMAS gasification stoves. This socialization activities attracted the attention community of Batu Belah Village and at the end of this socialization, the team gave gasification stoves to the local community as an effort to apply the technology.